2023
DOI: 10.1002/iid3.782
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid regulates immune response in a mouse model of rheumatoid arthritis

Abstract: Introduction Previous studies revealed that gallic acid (GA) exerts anti‐inflammation and immuno‐regulatory properties. This study aims to explore the pharmacological activities of GA in collagen‐induced arthritis (CIA) mouse model. Methods Male DBA/1J mice were used to construct the CIA model. The mice were administrated with GA for 3 weeks. Clinical arthritis scores and hind paw volume were evaluated over the experimental period. qPCR and Western blot analysis were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Moreover, cinnamic acid modulates inflammatory cytokines in adipose tissue, the liver, the hypothalamus, and decreases TNF-α in serum [34]. Gallic acid is known for its strong free radical scavenging activities and antiinflammatory properties; it has also shown immunomodulatory effects, as supported by a decrease in the inflammation cytokines and an increase of anti-inflammatory cytokines [35]. Additionally reported data stated that rutin has an immune regulatory effect, which can regulate cytokines and immune-related signaling pathways and cause a strong enhancement of antibody levels, increase immunoglobulin levels, and restore the functioning of leucocytes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cinnamic acid modulates inflammatory cytokines in adipose tissue, the liver, the hypothalamus, and decreases TNF-α in serum [34]. Gallic acid is known for its strong free radical scavenging activities and antiinflammatory properties; it has also shown immunomodulatory effects, as supported by a decrease in the inflammation cytokines and an increase of anti-inflammatory cytokines [35]. Additionally reported data stated that rutin has an immune regulatory effect, which can regulate cytokines and immune-related signaling pathways and cause a strong enhancement of antibody levels, increase immunoglobulin levels, and restore the functioning of leucocytes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a shift in the Th17/Treg cell balance towards the Treg cell side has been shown to lead to increased levels of IL‐10 and TGF‐β, while decreasing IL‐17 levels 11 . The treatment of gallic acid modulates the Th17/Treg cell balance, resulting in increased expression of IL‐10 and TGF‐β, and reduced levels of IL‐17 33 . Consistent with previous studies, our findings demonstrated significant positive correlations between serum TGF‐β1 and IL‐17 and IL‐21 levels in CSU patients, while serum IL‐35 levels exhibited significant negative correlations with IL‐17 and IL‐21 levels.…”
Section: Discussionmentioning
confidence: 99%